2019
DOI: 10.1080/00224499.2019.1669135
|View full text |Cite
|
Sign up to set email alerts
|

Discrepant Responding across Measures of College Students’ Sexual Victimization Experiences: Conceptual Replication and Extension

Abstract: Sexual violence victimization affects approximately 1 in 5 college women and 1 in 6 college men; however, rates of sexual victimization vary widely, in part due to measurement issues. The present study is the first to compare the Sexual Experience Survey-Short Form Victimization to a measure of sexual victimization designed to capture gender differences, the Post-Refusal Sexual Persistence Scale-Victimization (PRSPS-V). Prior research has compared the perpetration versions of these questionnaires and found lar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
2
17
1
Order By: Relevance
“…One version presented the coercive tactics in a hierarchical order from least to most severe, the other presented the tactics in a random order. Their results found no significant differences in the overall prevalence rates identified by the different formats, but rates were substantially higher than the rates identified in an earlier study using the standard version of the SES by Koss et al (2007) in which the items lead with the sexual acts rather than the coercive tactics (Anderson & Delahanty, 2020).…”
Section: Explanations Of Order Effects In Surveysmentioning
confidence: 61%
“…One version presented the coercive tactics in a hierarchical order from least to most severe, the other presented the tactics in a random order. Their results found no significant differences in the overall prevalence rates identified by the different formats, but rates were substantially higher than the rates identified in an earlier study using the standard version of the SES by Koss et al (2007) in which the items lead with the sexual acts rather than the coercive tactics (Anderson & Delahanty, 2020).…”
Section: Explanations Of Order Effects In Surveysmentioning
confidence: 61%
“…Acknowledging this challenge, a growing body of research has examined the impact of methodological decisions on the prevalence rates derived from different measures of sexual aggression. Studies have examined the convergence of prevalence rates assessed by different instruments (Anderson & Delahanty, 2020;Testa et al, 2015) and shown that variations in item format and number of items produce different prevalence figures (Cook et al, 2011;Kolivas & Gross, 2007;Koss, 1993;Krahé et al, 2014). Other studies have found that using behaviorally specific questions produce significantly higher prevalence rates compared with narrow direct questions regarding attempted or completed rape (e.g., "Have you been raped?")…”
mentioning
confidence: 99%
“…Made to penetrate victimization may be particularly relevant to understanding bisexual men’s experiences, as some data suggests this behavior is perpetrated almost exclusively by heterosexual women ( Anderson et al, 2020 ; Weare, 2018 ). Further, research suggests that currently available questionnaires, such as the iterations of the Sexual Experiences Survey, may be inherently gendered and contain some degree of heterosexist bias because the development of these questionnaires largely excluded SGM populations ( Anderson & Delahanty, 2020 ; Anderson et al, 2021 ). Indeed, research from the IPV literature suggests there may be tactics of violence specific to the experiences of SGM people, such as threatening to “out” someone (i.e., reveal their sexual identity without their consent; Balsam & Szymanski, 2005 ; Dyar et al, 2021 ).…”
Section: Measurement and Methodology Issues In Sexual Violencementioning
confidence: 99%